WIND ENERGY IN SLOVENIA AND AUSTRIA - Brinovar, Iztok (Journal of Energy Technology, 2024)
Due to obvious climate changes and increasing needs for electrical energy, increasing attention is dedicated to the use of renewable energy sources, which include wind energy. This article presents the current situation of wind energy exploitation in Slovenia and Austria and their national objectives for the near future. In contrast to Slovenia, Austria has a long tradition of wind energy use, due to its high wind energy potential. As member states of the European Union, Slovenia and Austria follow the European energy policy and its objectives of sustainable, competitive, and secure supplies of energy. This article deals with Slovenian and Austrian national energy policies and their incentive programs that encourage the exploitation of wind energy and other renewable energy sources. Both countries are increasing their renewable energy production by implementing financial support mechanisms, mostly feed-in tariffs, premium tariffs and loans.